Evaluation of Differentiated Learning in Economics Subjects Using the CIPP Model - Indriyana, Karina Purnama; Saputri, Renita; Herawan, Endang; Rusdiyana, Rusdiyana (LPPPIPublishing, 2024)
The advantages and disadvantages of the application of differentiated learning in economics subjects can be known from the data obtained and we can make improvements to the shortcomings that occur in this learning. The purpose of this study is to understand the implementation of differentiated learning in schools through the CIPP evaluation model, identify barriers and challenges faced, and provide recommendations to improve its implementation. The method used is descriptive qualitative. Data collection techniques were obtained from interviews, observations, and documentation. This data analysis process proceeds from facts to theory. The result of this research is the implementation of differentiated learning using the CIPP evaluation model at SMAN 1 Cilimus can improve the quality of learning. The input aspect of the teacher has succeeded in adjusting the curriculum and learning style according to the needs and interests of different students. The process aspect of the teacher has successfully played an important role in the learning process by becoming a facilitator for students to get a unique learning atmosphere, collaborative, constructive feedback. Students experienced increased understanding, critical thinking, encouragement to learn, and improved posttest results according to the product component. The results of this study make an important contribution to building more inclusive and flexible school learning methods through differentiated learning. It is hoped that this research can serve as a guideline and inspiration for other schools to implement differentiated learning and support the diversity of their students.